Prospective comparison of 68Ga-DOTA-ibandronate and bone scans for detecting bone metastases in breast cancer - Xiang, Feifan; Zhang, Yue; Tan, Xiaoqi; Yan, Yuanzhuo; Liu, Huipan; Ma, Wenzhe; Chen, Yue (Frontiers in Oncology, 2024)
Introduction 68Ga labeled DOTA-Ibandronate (68Ga-DOTA-IBA) positron emission tomography/computed tomography (PET/CT), is a novel bone-targeting imaging tracer and promising diagnostic method for bone metastases detection. Therefore, this study aimed to compare 68Ga-DOTA-IBA PET/CT to the 99mTc-MDP whole-body bone scan (WBBS) for detecting bone metastases in breast cancer (BC). Materials and methods In this prospective study, 45 women with BC underwent imaging via 68Ga-DOTA-IBA PET/CT and 99mTc-MDP WBBS. Clinical and demographic information as well as BC imaging features were recorded. The two methods were compared in terms of their detection rate for bone metastases and the number of lesions. Results The 45 women were aged 53.5 ± 11.0 years. The bone metastases detection rate with 68Ga-DOTA-IBA PET/CT was 100% (45/45) and with 99mTc-MDP WBBS was 95.6% (43/45). A total of 546 bone metastases lesions were detected. The lesion detection rate using 68Ga-DOTA-IBA PET/CT was 100% (546/546) and using 99mTc-MDP WBBS was 67.8% (370/546). More lesions were found at each site via 68Ga-DOTA-IBA than via 99mTc-MDP WBBS. Conclusions 68Ga-DOTA-IBA PET/CT is a more sensitive method than 99mTc-MDP WBBS for assessing bone metastases in BC and may therefore represent a useful imaging technique for bone metastases, while offering a visual basis for 177Lu-DOTA-IBA diagnosis and therapy response assessments for BC. Further validation using a broader study cohort is warranted to confirm these findings. Clinical trial registration https://www.chictr.org.cn/showproj.html?proj=170163, identifier ChiCTR2200064487.